Tolerogenic dendritic cells that inhibit autoimmune arthritis can be induced by a combination of carvacrol and thermal stress. - Rachel Spiering; Ruurd van der Zee; Josée Wagenaar; Dimos Kapetis; Francesca Zolezzi; Willem van Eden; Femke Broere (PLoS ONE, 2012)
Tolerogenic dendritic cells (DCs) can induce regulatory T cells and dampen pathogenic T cell responses. Therefore, they are possible therapeutic targets in autoimmune diseases. In this study we investigated whether mouse tolerogenic DCs are induced by the phytonutrient carvacrol, a molecule with known anti-inflammatory properties, in combination with a physiological stress. We show that treatment of DCs with carvacrol and thermal stress led to the mRNA expression of both pro- and anti-inflammatory mediators. Interestingly, treated DCs with this mixed gene expression profile had a reduced ability to activate pro-inflammatory T cells. Furthermore, these DCs increased the proportion of FoxP3(+) regulatory T cells. In vivo, prophylactic injection of carvacrol-thermal stress treated DCs pulsed with the disease inducing antigen was able to suppress disease in a mouse model of arthritis. These findings suggest that treatment of mouse bone marrow derived DCs with carvacrol and thermal stress induce a functionally tolerogenic DC that can suppress autoimmune arthritis. Herewith carvacrol seems to offer novel opportunities for the development of a dietary based intervention in chronic inflammatory diseases.